Ultrasound and MRI of Pediatric Ocular Masses with Histopathologic Correlation - Brennan, Rachel C. (2012)
We review our experience with unusual ocular pathologies mimicking retinoblastoma that were referred to our institution over the past two decades. After presenting the imaging anatomy of the normal eye, we discuss pertinent clinical and pathological features, and illustrate the ultrasound and magnetic resonance imaging appearance of retinoblastoma, medulloepithelioma, uveal melanoma, persistent fetal vasculature, Coats disease, corneal dermoid, retinal dysplasia and toxocara granuloma. Features useful in discriminating between these entities are emphasized.